B-scan ultrasonic testing of rivets in multilayer structures based on short-time Fourier transform analysis. (November 2018) - Le, Minhhuy; Kim, Jungmin; Kim, Sejin; Lee, Jinyi
Highlights: Ultrasonic testing for inspection of damage of rivet in a multilayer structure. Ultrasonic testing system for inspection of aircraft. B-scan spectrogram based on Short-Time Fourier Transform. Auto detection algorithm and damage depth evaluation. Abstract: This paper proposes an ultrasonic testing system for inspection of pitting corrosion cracks in rivets of multilayer structures. The inspection operates in B-scan mode with an ultrasonic probe passing over the rivet head. The ultrasonic signal is analyzed in the frequency domain using the short-time Fourier transform. To analyze and evaluate the effectiveness of the system, B-scan data obtained by scanning a rivet head within ±1 mm from the rivet head center will be used and an algorithm to evaluate the existence of cracks in the rivet using B-scan data will be proposed. To evaluate the performance of the system, its probability of detection (POD) is analyzed. With the data obtained at a scanning speed of 6 mm/s, the system could detect artificial pitting corrosion cracks with areas of 47.28% of the rivet body cross-section area with 90/95% POD.